A FITTED DEVIATING ARGUMENT AND INTERPOLATION SCHEME FOR THE SOLUTION OF SINGULARLY PERTURBED DIFFERENTIALDIFFERENCE EQUATION HAVING LAYERS AT BOTH ENDS. (2021) - SINGH, RAGHVENDRA PRATAP; REDDY, Y. N.
No abstract available